Pengelolaan Laboratorium IPA SMP Negeri 2 Muara Rupit Kabupaten Musi Rawas Utara Tahun 2020 - N., Najemah (LPPM UNIVERSITAS PGRI SILAMPARI, 2020)
This study aims to determine the management of the Natural Sciences laboratory at SMP Negeri 2 MuaraRupit in 2020, including: (1) science laboratory planning; (2) regulating the use of science laboratories; (3) evaluation and supervision of the use of natural science laboratories. This research is a qualitative descriptive study. Data collection techniques using interviews, observation, and documentation. Data were analyzed using models from Miles and Huberman with the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that: (1) Planning a science laboratory includes the procurement of science laboratory equipment / materials carried out by the science laboratory coordinator and science teacher through a needs analysis based on priority scale adjusted to available funds. Plans for the use of science laboratories in learning science are not detailed up to the daily schedule, but there is only a monthly schedule. (2) Arrangements for the use of natural science laboratories include: (a) procedure for the use of natural science laboratories, (b) preparation of natural science tools / materials, (c) storage of natural science tools / materials, (d) maintenance / maintenance of natural science laboratories carried out by the Natural Sciences laboratory coordinator set forth in writing in a laboratory order. (3) Supervision carried out by the principal is still limited to know the implementation of teaching and learning activities in the laboratory, not yet leading to the process of managing the science laboratory. Whereas for the evaluation of the management of the Natural Sciences laboratory carried out by the Natural Sciences Laboratory Coordinator, it is only limited to evaluating the appropriateness of the equipment and the availability of Natural Sciences, the results of which are used as a reference in the procurement of equipment in the following year.